The Influence Of Social Influencer Marketing On Consumer Purchase Intention: An Analysis On Young Adults - Nur Fatimatuzzahra Mohd Fouzi; Muhamad Azrin Nazri; Mohammad Tahir Zainuddin (Universal Publishers - Boca Raton, Florida, USA, 2024)
Non-Indexed Publication